Perspectives of HPV vaccination among young adults: a qualitative systematic review and evidence synthesis protocol - Purnima Madhivanan; Jonathan Smith; Namoonga M Mantina; Flavia Nakayima Miiro; Deborah Jean McClelland; Priscilla Anne Magrath (BMJ Open)
Introduction Human papillomavirus (HPV) is the causative agent of nearly all cervical cancers. Despite the proven safety and efficacy of HPV vaccines in preventing HPV-related cancers, the global vaccine coverage rate is estimated to only be 15%. HPV vaccine coverage rates are more actively tracked and reported for adolescents 17 years and younger but there is still a critical window of opportunity to intervene and promote HPV vaccination among young adults aged 18–26 years who are still eligible to be vaccinated. This protocol for a qualitative evidence synthesis aims to review perspectives of HPV vaccination among young adults (18–26 years) and identify facilitators and barriers that influence HPV vaccination uptake and decision-making.Methods and analysis Seven databases will be searched from 1 January 2006 to the date of final search. For inclusion, studies must report HPV vaccination perspectives of young adults aged 18–26 years and use qualitative study methods or analysis techniques. Studies will be screened in a two-stage process guided by the eligibility criteria. Final included studies will be evaluated for methodological strengths and limitations using the Critical Appraisal Skills Programme quality assessment tool for qualitative studies. After data extraction, framework analysis will be used to analyse the data applying the socioecological model. Finally, the Grading of Recommendations Assessment, Development and Evaluation - Confidence in the Evidence from Reviews of Qualitative research will be applied to evaluate the confidence in synthesised qualitative findings. The methodology of this review follows the Cochrane Handbook guidelines on qualitative evidence syntheses.Ethics and dissemination Formal ethical approval is not required for this study. Findings will be disseminated through peer-reviewed publications, conference presentations and professional networks.PROSPERO registration number CRD42023417052.